Effect of spacing on seed yield and physiological traits in moth bean (Vigna aconitifolia) - BURMAN, UDAY; GARG, B K; KATHJU, S (The Indian Journal of Agricultural Sciences, 2014)
An experiment was conducted during the rainy season of 1997 and 1998 to study the effect of 2 spacings (30 cm x 15 cm and 45 cm x 10 cm) on moth bean [Vigna aconitifolia (Jaeq.) Marcchal] genotypes (’Maru Moth’, ’RMO 40’ and ’CZM 32E’) under rainfed conditions. Closer spacing (30 cm x 15 cm) crop showed higher seed yield (652.5 kg/ha) and dry-matter production (1 812 kg/ha) than 45 cm x 10 cm spacing (seed yield 529 kg/ha and 1 501.5 kg/ha). This was attributed to better utilization of available soil moisture and maintenance of favourable plant water status, which led to high photosynthetic efficiency (17.1 umol/m2/sec) and chlorophyll content (4.50 mg/g dry weight). Genotype ’CZM 32E’ showed better seed yield (690 kg/ha), higher photosynthetic rate (17.1 p mol/m2/sec) and favourable plant water status than ’Maru Moth’ and ’RMO 40’ during both the years.